ADDRESSING THE DEBATE ON THE ECO-FRIENDLINESS OF INDONESIAN BATIK BY WATER FOOTPRINT APPROACH - Handayani, Widhi; Widianarko, Yohanes Budi; Pratiwi, Alberta Rika (Journal of Environmental Science and Sustainable Development, 2023)
The Indonesian batik is an intangible cultural heritage that contributes to the country's economy but raises environmental pollution. Synthetic dyes are considered to cause pollution, and the natural counterpart is recommended to replace it because natural dyes are considered more eco-friendly than synthetic ones. Therefore, this study examined the Blue Water Footprint (BWF) and Grey Water Footprint (GWF) of the batik household industry by applying synthetic dyeing and comparing the result to the natural dyeing from previous studies. This research used the Water Footprint accounting approach based on the Water Footprint Network, which involves identifying the batik process followed by measuring and calculating the consumptive water use representing BWF and degradative water use representing GWF. The BWF of batik-making process applying of synthetic dyes was 1000.914 L/day or 9.223 L/pc, and the GWF was 12,877.215 – 18,003.118 L/day or 95.39 – 142.88 L/pc. Washing consumes water most responsible for the high BWF, while dilution water for dye solution and wastewater dominates the portion of GWF. Applying both dyes produces wastewater whose quality exceeds the acceptable limit the Indonesian government sets, indicating that eco-friendliness should not be directly associated with synthetic or natural dyes. The selection of synthetic or natural dyes alone for batik production is not recommended since dyeing might be related to environmental issues and market preferences. The main problem lies in the batik artisans' general assumption regarding eco-friendliness linked to specific dyes, which needs to be improved by increasing water use efficiency with technology. Future research must focus on finding innovations to reduce water use in batik processing.